Preparation and Characterization Of Untreated Waste Palm Oil/Diesel Fuel Blend - Ali, M. I.; Abdullah, S.; Mohamad, T. I; W. Daud, W. R. (Journal of Mechanical Engineering and Technology (JMET), 2015)
Some diesel engines can run on some kinds of vegetable oil under some conditions without problems. To use vegetable oils in diesel engine without modification, it is necessary to make sure that the vegetable oils properties must be similar to diesel fuel. In this study, palm oil that has been used several times for frying purposes is investigated for the utilization as an alternative fuel for diesel engines. The waste palm oil has a variety of qualities, possess properties different from that of neat oils. Higher impurities of the used oils make them different from neat vegetable oil. The high viscosity of the waste palm oil was decreased by blending with diesel. Two different previous uses of waste palm oil were blend with diesel. The blends of varying proportions of waste palm oil and diesel were prepared, analyzed and compared with diesel fuel and the waste palm oil ethyl ester. The properties of the blends such as heating value, viscosity, specific gravity, etc. were determined. It was found that blending waste palm oil with diesel reduces the viscosity and different previous uses of waste palm oil significantly affected the properties of the blended fuels. From the properties test results it has been established that blends containing 5 to 40% of waste palm oil in diesel yielded the properties closely matching that of diesel.